2017
DOI: 10.1038/nmat5009
|View full text |Cite|
|
Sign up to set email alerts
|

Robust resistive memory devices using solution-processable metal-coordinated azo aromatics

Abstract: Non-volatile memories will play a decisive role in the next generation of digital technology. Flash memories are currently the key player in the field, yet they fail to meet the commercial demands of scalability and endurance. Resistive memory devices, and in particular memories based on low-cost, solution-processable and chemically tunable organic materials, are promising alternatives explored by the industry. However, to date, they have been lacking the performance and mechanistic understanding required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
227
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(241 citation statements)
references
References 47 publications
6
227
1
Order By: Relevance
“…Uniform switching means that the dispersion range is narrow and centralized. In general, the spread in switching voltages will be expressed by [∆ V (2σ)/ V mean ] value . The variation [∆ V (2σ)/ V mean ] in the switch‐on and switch‐off voltages of c‐AFM device is <10%, and the variation of our NQD device cannot reach so good.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uniform switching means that the dispersion range is narrow and centralized. In general, the spread in switching voltages will be expressed by [∆ V (2σ)/ V mean ] value . The variation [∆ V (2σ)/ V mean ] in the switch‐on and switch‐off voltages of c‐AFM device is <10%, and the variation of our NQD device cannot reach so good.…”
mentioning
confidence: 99%
“…Among the methods proposed, integration of the metallic nanoparticles, such as Ag, Au, Mo, Ru, Co, and Cu, as charge‐trapping materials has been found very efficient to improve the uniformity of the RS among different cycles . Nanoscale characterization of RS with conductive atomic force microscope (c‐AFM) demonstrated that the improvement of the performance with introduction of metal nanoparticles is due to the enhancement of electric field . However, the metal nanoparticles formed with direct physical vapor deposition show large size distribution and are randomly distributed in the films due to the thermal dynamic process.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In particular in the non-conventional space of smart applications requiring conformal attachment on non-flat surfaces such as on-body wearables, the notion of system on plastics (SOP) incorporating neuromorphic computing provides a potential solution. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, current memristor manufacturing technologies such as chemical vapor deposition (CVD), [7,8,[11][12][13] spin-coating, [14,15] or entire transfer [16] impose enormous challenges on flexible substrates as they suffer from high temperature, low yield and complex sacrificial layer removal. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]…”
mentioning
confidence: 99%
“…The bottom w-rGO electrode was grounded and the bias was applied to the top Al electrode during the measurement. [16] To estimate stability and reproducibility, the devices were placed into ON and OFF states at time zero and currents were sampled at 350 K, which is the standard semiconductordevice test temperature. Initially, the two devices exhibited a high resistance state (OFF state) at low voltage (0-0.9 V) region.…”
Section: Doi: 101002/aelm201800503mentioning
confidence: 99%